13 Natural history and clinical significance of infarct zone extracellular volume and remodelling in survivors of acute STEMI. (17th November 2015) - Carberry, J; Carrick, D; Haig, C; Rauhalammi, S; Ahmed, N; Mordi, I; McEntegart, M; Petrie, MC; Eteiba, H; Hood, S; Watkins, S; Lindsay, M; et al.
Abstract : Background: The natural history and clinical significance of myocardial extracellular volume (ECV) in infarcted myocardium post-STEMI is uncertain. ECV can be estimated by cardiac magnetic resonance imaging (CMR). We measured infarct ECV of STEMI survivors, and assessed the relationships with clinical findings. Methods: STEMI survivors were enrolled in a cohort study (BHF MR-MI study – NCT02072850 ). CMR was performed at 1.5 Tesla (Siemens MAGNETOM Avanto) 2 days and 6 months post-MI. T1 MOLLI mapping was performed pre- and 15 min post-contrast (0.15 mmol/kg gadoterate meglumin). ECV was calculated as the difference in relaxation rate (R1 = 1/T1) for myocardium and LV blood pool pre- vs. post-contrast, corrected for haematocrit (HCT). The percentage change in infarct ECV was calculated (%ΔECV). Results: 129 patients (59 ± 11 years; 98 (76%) male) were included. Infarct ECV at baseline and follow-up was similar (49.5(9.3)% vs. 49.4 ± = (10.9)%; p = 0.904). The within-subject change in ECV varied markedly (1.0% (20.0%)). In multiple linear regression, TIMI coronary flow grade 2 pre-PCI, TIMI coronary flow grade 3 pre-PCI, a history of previous PCI and initial infarct size were independently associated with%ΔECV (all p < 0.05). At 6 months, LV end-diastolic volume increased on average by 2(25) ml. An increase in infarct zone ECV was associated with an increasing LV end-diastolic volume (0.30 (0.11, 0.48); p = 0.002). Conclusion: %ΔECV is associated with measures of MI severity, and portends worsening LV volume. Infarct ECV represents a novel biomarker for infarct characterisation in STEMI patients.